Women Veterans' experiences discussing household firearms with their intimate partners: collaborative, devalued, and deferential relational types - Evan R. Polzer; Carly M. Rohs; Suzanne M. Thomas; Ryan Holliday; Christin N. Miller; Joseph A. Simonetti; Katherine M. Iverson; Lisa A. Brenner; Lindsey L. Monteith (BMC, 2023)
Abstract Background Rates of firearm suicide have increased among women Veterans. Discussing firearm access and reducing access to lethal means of suicide when suicide risk is heightened are central tenets of suicide prevention, as is tailoring suicide prevention strategies to specific populations. While research has begun to explore how to optimize firearm lethal means safety counseling with women Veterans, there is limited knowledge of women Veterans' perspectives on including their intimate partners in such efforts. This gap is notable since many women Veterans have access to firearms owned by other household members. Understanding women Veterans' experiences and perspectives regarding including their partners in firearm lethal means safety conversations can provide important information for tailoring firearm lethal means safety counseling for women Veterans. Methods Qualitative interviews were conducted with 40 women Veterans with current or prior household firearm access. Interview questions focused on the roles of women Veterans' partners in household firearm access and storage, as well as women Veterans' perspectives regarding including intimate partners in firearm lethal means safety counseling. Inductive thematic analysis was performed. Results Three relational types characterized how household firearms were discussed between women Veterans and their partners: collaborative, devalued, and deferential. These types were distinguished via women Veterans' agency in decision-making related to household firearms, partners' receptivity to women Veterans' mental health or trauma histories, and willingness (or lack thereof) of partners to change household firearm access and storage considering such histories. Intimate partner violence was common in the devalued relational subtype. Conclusions Findings extend knowledge regarding the context of women Veterans' household firearm access, including relational dynamics between women Veterans and their partners. The acceptability, feasibility, challenges, and facilitators of including women Veterans' partners in firearm lethal means safety efforts likely vary for each relational type. For example, in dyads with a collaborative dynamic, incorporating partners may create opportunities for increased firearm safety, whereas including partners in devalued dynamics may present unique challenges. Research is warranted to determine optimal methods of navigating firearm lethal means safety counseling in the presence of each relational dynamic.